2011
DOI: 10.1007/s00425-011-1551-4
|View full text |Cite
|
Sign up to set email alerts
|

Experimental sink removal induces stress responses, including shifts in amino acid and phenylpropanoid metabolism, in soybean leaves

Abstract: The repeated removal of flower, fruit, or vegetative buds is a common treatment to simulate sink limitation. These experiments usually lead to the accumulation of specific proteins, which are degraded during later stages of seed development, and have thus been designated as vegetative storage proteins. We used oligonucleotide microarrays to assess global effects of sink removal on gene expression patterns in soybean leaves and found an induction of the transcript levels of hundreds of genes with putative roles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…Previous sink removal studies found upregulation of lipoxygenase genes vlxA , vlxB , vlxC , vlxD , and vlxE in sink‐limited leaves after anthesis, but expression of these genes decreases after anthesis when sinks are present (Bunker et al ; Stephenson, Bunker, Dubbs, & Grimes ; Turner et al ). In the present experiment, lipoxygenase genes exhibited some of the largest magnitudes of upregulation in both depodded and sterile soybeans, which supports a role for these genes beyond the wounding response, possibly in vegetative development and storage (Tranbarger, Franceschi, Hildebrand, & Grimes ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous sink removal studies found upregulation of lipoxygenase genes vlxA , vlxB , vlxC , vlxD , and vlxE in sink‐limited leaves after anthesis, but expression of these genes decreases after anthesis when sinks are present (Bunker et al ; Stephenson, Bunker, Dubbs, & Grimes ; Turner et al ). In the present experiment, lipoxygenase genes exhibited some of the largest magnitudes of upregulation in both depodded and sterile soybeans, which supports a role for these genes beyond the wounding response, possibly in vegetative development and storage (Tranbarger, Franceschi, Hildebrand, & Grimes ).…”
Section: Discussionmentioning
confidence: 96%
“…A series of sink removal studies have been conducted in soybean with particular interest in how sink limitation alters yield or seed protein accumulation (Egli, Gossett, & Leggett ; Kaschuk, Hungria, Leffelaar, Giller, & Kuyper ; McAlister & Krober ; Mondal et al ; Turner et al ; Wittenbach ). These studies measured physiological traits such as seed number, seed weight, carbohydrate concentration and movement, photosynthesis, and leaf and stem composition.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was reported that GABA could be high in the leaves after sink removal in soybean (Turner et al, 2012). These results show that apex removal affects nitrogen metabolism in roots, suggesting that amino acids synthesis from aspartate and glutamate pathways are enhanced.…”
Section: Asparagine and Sugars Are Involved In Axis II Nutrition And mentioning
confidence: 71%
“…Phenylpropnoid compounds are associated with many processes such as plant development and plant defense against hostile conditions (Korkina, 2007;Solecka, 1997). Genes related to phynelpropanoid metabolism pathways have been reported to be up-regulated under pathogenic or wounding events (Turner et al, 2012). Phenylpropanoids have been also investigated as a potential cancer treatment and chemopreventive agents (Bruyère et al, 2011;Itoigawa et al, 2004;Kim et al, 2011).…”
Section: Discussionmentioning
confidence: 99%